2005
DOI: 10.1126/science.1106469
|View full text |Cite
|
Sign up to set email alerts
|

Human Symbionts Use a Host-Like Pathway for Surface Fucosylation

Abstract: The mammalian intestine harbors a beneficial microbiota numbering approximately 10(12) organisms per gram of colonic content. The host tolerates this tremendous bacterial load while maintaining the ability to efficiently respond to pathogenic organisms. In this study, we show that the Bacteroides use a mammalian-like pathway to decorate numerous surface capsular polysaccharides and glycoproteins with l-fucose, an abundant surface molecule of intestinal epithelial cells, resulting in the coordinated expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
261
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(271 citation statements)
references
References 16 publications
9
261
1
Order By: Relevance
“…Another feature of the ability of BT3172 to sense the neighboring polysaccharide landscape is that it can modulate "mimicry" so that the surface polysaccharide structure of the bacterium can be altered to match the surrounding landscape, possibly allowing the bacterium to avoid eliciting a host immune response (68).…”
Section: Environmental Sensing Systemsmentioning
confidence: 99%
“…Another feature of the ability of BT3172 to sense the neighboring polysaccharide landscape is that it can modulate "mimicry" so that the surface polysaccharide structure of the bacterium can be altered to match the surrounding landscape, possibly allowing the bacterium to avoid eliciting a host immune response (68).…”
Section: Environmental Sensing Systemsmentioning
confidence: 99%
“…Analyses of bacteria metabolically labeled with 3 H-fucose and AAL probing of blots were performed as described (5). Glycoproteins were stained in gel with the Pro-Q Emerald 300 Glycoprotein Stain (Invitrogen, Carlsbad, CA).…”
Section: Analysis Of Products Separated By Sds/pagementioning
confidence: 99%
“…The importance of these fucosylated molecules to the Bacteroides is demonstrated by the defect in intestinal colonization by a B. fragilis mutant that cannot add fucose to capsular polysaccharides and glycoproteins (5). An fkp-specific probe hybridized with the genomic DNA of four other related species and each of these organisms incorporates exogenous fucose into glycoproteins (5). The amount of exogenous fucose incorporated into the glycoproteins of the numerically abundant colonic species Bacteroides distasonis far exceeded that of the other species tested, making it an interesting subject for further study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Positive interactions would promote the persistence of a core microbiota, while negative interactions would reduce microbial co-occurrence, potentially leading to variation in microbiota composition among host individuals. Specific instances of competition, metabolite crossfeeding and other among-microbe interactions are known, (for example, Coyne et al, 2005;Donohoe et al, 2011;Rosenthal et al, 2011), but the overall contribution of positive and negative interactions to the microbial community has rarely been considered. Exceptionally, Faust et al (2012) found that most interactions in the human microbiota are negative, suggesting that processes such as competition and niche differentiation may be important determinants of community structure in this system.…”
Section: Introductionmentioning
confidence: 99%